Clinical Significance of Tumor-Infiltrating T Cells and Programed Death Ligand-1 in Patients with Pancreatic Cancer. (21st October 2019) - Yoshida, Sayumi; Ito, Zensho; Suka, Machi; Bito, Tsuuse; Kan, Shin; Akasu, Takafumi; Saruta, Masayuki; Okamoto, Masato; Kitamura, Hiroaki; Fujioka, Shuichi; Misawa, Takeyuki; Akiba, Tadashi; et al.
Abstract: The associations of the immunological status of the pancreatic ductal adenocarcinoma (PDA) microenvironment with prognosis were assessed. A high tumor-infiltrating lymphocyte (TIL) density was associated with a better prognosis. Importantly, even with a high density of TILs, the PDA cells with programed cell death-ligand 1 (PD-L1) expression showed a worse prognosis than the patients with negative PD-L1 expression. A significant association between a better prognosis and a tumor microenvironment with a high TIL density/negative PD-L1 expression was observed. Assessments of a combined immunological status in the tumor microenvironment may predict the prognosis of PDA patients following surgical resection.